2022
DOI: 10.54394/tmuv3384
|View full text |Cite
|
Sign up to set email alerts
|

The current state of research on the two-way linkages between productivity and well-being

Abstract: Interest in the topic of well-being has burgeoned in recent years as the weaknesses of gross domestic product (GDP) per capita as a proxy for well-being have become more apparent. At the same time, the global economy has experienced a productivity slowdown. Since productivity growth is recognized as being by far the most important long-term source of sustainable gains in living standards, this development has implications for the future of living standards around the world. These two developments raise a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Real income growth, in turn, boosts tax revenue, which can be spent on public infrastructure and services and on transfer payments. The link between productivity growth and well-being has, however, been weakening in recent decades, owing to both the slowdown in productivity growth and the decoupling of productivity from median wages (Sharpe and Mobasher Fard 2022). The same study finds that well-being is also a driver of productivity.…”
Section: Sourcementioning
confidence: 91%
See 1 more Smart Citation
“…Real income growth, in turn, boosts tax revenue, which can be spent on public infrastructure and services and on transfer payments. The link between productivity growth and well-being has, however, been weakening in recent decades, owing to both the slowdown in productivity growth and the decoupling of productivity from median wages (Sharpe and Mobasher Fard 2022). The same study finds that well-being is also a driver of productivity.…”
Section: Sourcementioning
confidence: 91%
“…Productivity growth is one of the most important drivers of economic and social wellbeing. Sharpe and Mobasher Fard (2022) offer an analysis of the two-way linkages between productivity and well-being, concluding that productivity growth -and the higher incomes and government revenues arising from it -contributes to higher levels of objective measures of material well-being, especially in developing countries. The most important channel through which productivity growth enhances well-being is by generating real income gains, both for workers in the form of real wages and for owners of capital through higher profits.…”
Section: Sourcementioning
confidence: 99%
“…Well-being represents the physical, mental and emotional facets of employee health, synergistically acting to affect individuals in a complex manner (DeJoy and Wilson, 2003;Grawitch et al, 2006). Thus, workplace well-being denotes all facets of working life, from the quality and safety of the physical environment, to the way workers feel about the work they do and their working environment, climate and organisation (Sharpe and Fard, 2022). Along these lines, Isham et al (2020), and Krekel et al (2019) following Human Relations Theory states that greater employee well-being is associated with improved morale, which, in turn, leads to higher productivity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Workplace well-being refers to all aspects of working life, such as: work quality, work environment, work climate and work organisation ( Sharpe and Fard, 2022). Well-being in the workforce has also been linked to higher levels of employee engagement, which, in turn, leads Aspects of work for apprentice employability to higher productivity (Haddon, 2018;Isham et al, 2020;Pfeffer, 2018;Sharpe and Fard, 2022). Employee well-being is a key factor in determining an organisation's long-term effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Wellbeing and productivity are closely interconnected. Research has shown a strong two-way link between productivity and wellbeing; better wellbeing has a strong and positive impact on productive performance in work, while the productivity gains from high performance also contribute to better wellbeing of people through higher incomes, life and job satisfaction (9). It is essential therefore, that challenges affecting the wellbeing of working people be addressed to foster better productivity.…”
Section: Introductionmentioning
confidence: 99%